2005
DOI: 10.2174/0929867054637617
|View full text |Cite
|
Sign up to set email alerts
|

Copper as a Biocidal Tool

Abstract: Copper ions, either alone or in copper complexes, have been used to disinfect liquids, solids and human tissue for centuries. Today copper is used as a water purifier, algaecide, fungicide, nematocide, molluscicide as well as an anti-bacterial and anti-fouling agent. Copper also displays potent anti-viral activity. This article reviews (i) the biocidal properties of copper; (ii) the possible mechanisms by which copper is toxic to microorganisms; and (iii) the systems by which many microorganisms resist high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
375
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 608 publications
(388 citation statements)
references
References 131 publications
1
375
0
12
Order By: Relevance
“…Also consistent with five independent CUP1 amplification events, there was very little CUP1 sequence heterogeneity and no CUP1-linked SNPs associated with CUP1 copy number or with copper resistance. We hypothesize that independent CUP1 gene amplification events, and increased copper resistance, have been selected by the agricultural use of fungicidal copper salts (Borkow and Gabbay 2005;Holb 2009;Mackie et al 2012) in natural S. cerevisiae environments. Similar to Warringer et al (2011), we observed CUP1 copy number association with copper resistance and that CUP1 copy number was responsible for ∼50% of copper resistance.…”
Section: Chromosomal Rearrangements Aneuploidy and Introgressionmentioning
confidence: 99%
“…Also consistent with five independent CUP1 amplification events, there was very little CUP1 sequence heterogeneity and no CUP1-linked SNPs associated with CUP1 copy number or with copper resistance. We hypothesize that independent CUP1 gene amplification events, and increased copper resistance, have been selected by the agricultural use of fungicidal copper salts (Borkow and Gabbay 2005;Holb 2009;Mackie et al 2012) in natural S. cerevisiae environments. Similar to Warringer et al (2011), we observed CUP1 copy number association with copper resistance and that CUP1 copy number was responsible for ∼50% of copper resistance.…”
Section: Chromosomal Rearrangements Aneuploidy and Introgressionmentioning
confidence: 99%
“…It is also a well-known bactericide, although the mechanisms involved in copper-mediated injury have not yet been resolved (Borkow & Gabbay, 2005;Macomber et al, 2007). In order to prevent copper damage, the cytoplasmic concentration of free copper must be negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyzed the capacity of reducing root intrusion into the emitters by incorporating microscopic copper particles during the manufacture of the emitters, as copper is known as a potent algaecide (Borkow and Gabbay 2005;Murray-Gulde et al 2002).…”
Section: Discussionmentioning
confidence: 99%